Analysis of practice of granting state and municipal services - N. L. Ashirbagina; A. I. Kovalyov; O. V. Frik (Вестник СибАДИ, 2017)
Providing state and municipal services to the public is a primary function in the activities of state and municipal government. It is the quality of the provision of public services to citizens assess the effects of the activities of state bodies and local authorities. This article discusses the practical aspects of such services.